Spiro Heterocyclic Compounds as Potential Anti-Alzheimer Agents (Part 2): Their Metal Chelation Capacity, POM Analyses and DFT Studies - Hadda, Taibi B.; Deniz, Fatma S.S.; Orhan, Ilkay E.; Zgou, Hsaine; Rauf, Abdur; Mabkhot, Yahia N.; Bennani, Brahim; Emam, Dalia R.; Kheder, Nabila A.; Asayari, Abdulrhman; Muhsinah, Abdullatif B.; Maalik, Aneela (Medicinal Chemistry, 2021)
Background: One of the best methods to treat Alzheimer disease (AD) is through the effective use of cholinesterase inhibitors as vital drugs due to the identification of acetylcholine deficit in the AD patients. Objective: The present study aims the investigation of spiro heterocyclic compounds as potential AD agents supported by their metal chelation capacity, POM analyses and DFT studies, respectively. Methods: The cholinesterase inhibition and metal chelation ability were performed on ELISA microtiter assay. Whereas, the B3LYP method with 6-31+G(d,p) basis set was implemented to study HOMOLUMO energy calculations. The pharmacokinetic properties of the synthesized molecules were studied through Petra, Osiris and Molinspiration (POM). Results: The six spiro (1-6) skeletons were tested for their inhibitory potential and metal-chelation capacity. Our findings revealed that the tested spiro skeletons exerted none or lower than 50% inhibition against both cholinesterases, while compound 4 proved to be the most active molecule with 57.21±0.89% of inhibition toward BChE. The spiro molecule 3 exhibited the highest metal-chelation capacity (9.12±5.26%). Molecular docking model for the most active molecule exhibited promising bindings with AChE and BChE’s active site pertained to hydrophobic hydrogen bonds and positive ionizable interactions. The POM analyses gave the information about the flexibility at the site of coordination of spiro compounds (1-6). Conclusion: The screening of spirocompounds (1-6) against cholinesterases revealed that some of them show considerable potential to inhibit AChE and BChE. Herein, we propose that the spiro molecules after further derivatization could serve interesting AD inhibitor drugs.
Keywords: anti-Alzheimer